Pharmacophore modeling, molecular docking and molecular dynamics simulations toward identifying lead compounds for Chk1. (October 2018) - Li, Yaping; Peng, Jiale; Zhou, Yeheng; Li, Penghua; Li, Yingying; Liu, Xingyong; Siddique, Abu Nasar; Zhang, Li; Zuo, Zhili
Graphical abstract: Highlights: Identified potential inhibitors of Chk1 by using similarity search, pharmacophore modeling, molecular docking and molecular dynamics simulations. A "similarity searching" strategy was performed for finding potential Chk1 inhibitors. A combination of fast docking program (LibDock) and accurate docking program (GOLD). Abstract: Checkpoint kinase 1 (Chk1), a serine/threonine protein kinase, plays an important role in G2/M checkpoint, which is a key regulator in response to DNA damage. In this study, the structure-based drug design approach and molecular dynamics (MD) simulations were used to explore potent Chk1 inhibitors. A series of the best fitting candidates were picked out from the Specs database. Out of these, five candidates were submitted for MD simulations to explore the stability of complex. The result indicates that these five candidates could be considered potential Chk1 inhibitors and represents a promising starting point for developing potent inhibitors of Chk1 for the treatment of tumor.